Znaczenie diagnostyczne klasyfikacji rozwojowych we wczesnym rozpoznaniu mózgowego porażenia dziecięcego = The diagnostic importance of diagnostic developmental classifications in the early diagnosis of cerebral palsy - Strączyńska, Agnieszka; Weber-Rajek, Magdalena; Radzimińska, Agnieszka; Strojek, Katarzyna; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Strączyńska Agnieszka, Weber-Rajek Magdalena, Radzimińska Agnieszka, Strojek Katarzyna, Goch Aleksander, Zukow Walery. Znaczenie diagnostyczne klasyfikacji rozwojowych we wczesnym rozpoznaniu mózgowego porażenia dziecięcego = The diagnostic importance of diagnostic developmental classifications in the early diagnosis of cerebral palsy. Journal of Education, Health and Sport. 2016;6(1):207-218. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45339 http://ojs.ukw.edu.pl/index.php/johs/article/view/45339 https://pbn.nauka.gov.pl/works/709894 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Znaczenie diagnostyczne klasyfikacji rozwojowych we wczesnym rozpoznaniu mózgowego porażenia dziecięcego The diagnostic importance of diagnostic developmental classifications in the early diagnosis of cerebral palsy Agnieszka Strączyńska1, Magdalena Weber-Rajek1, Agnieszka Radzimińska1, Katarzyna Strojek1, Aleksander Goch1, Walery Zukow2 1Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Streszczenie Skale rozwojowe są powszechnie stosowane w programie wczesnej interwencji. Zaleca się ich stosowanie w ocenie motorycznej niemowląt i małych dzieci, jako podstawowe narzędzia diagnostyczne i prognozujące cel terapii. Badanie neurorozwojowe mają przede wszystkim na celu wykrywanie zagrożenia występowania mózgowego porażenia dziecięcego i innych deficytów wynikających z zaburzenia ośrodkowego układu nerwowego. W dostępnej literaturze opisano wiele klasyfikacji rozwojowych jednak nie zawsze odznaczają się one wysoką specyficznością i czułością w określaniu poziomu nieprawidłowości. Praca ma na celu przybliżenia cech charakterystycznych poszczególnych testów diagnostycznych z oceną ich rzetelności i trafności zastosowania we wczesnym rozpoznaniu mózgowego porażenia dziecięcego. Słowa kluczowe: mózgowe porażenie dziecięce, diagnostyka niemowlaków, testy przesiewowe, zaburzenia rozwoju. Abstract The developmental scales are widely used in the early intervention. It They areis recommended to be for used in the motor assessments in of infants and young children, as the basic diagnostic tools and forecasting the therapeutic target. The neurodevelopmental examinations are primarily aimed at detecting the risk (risk factors) of cerebral palsy and other deficits consequent resulting from disorders of the central nervous system. The literature describes many developmental classifications, however, not always are they are characterized by high specificity and sensitivity in determining the level of disabilities. The paper aims to introduce the characteristics of individual diagnostic tests and simultaneously with evaluation of their reliability and application validity of the application in early diagnosis of cerebral palsy. Keywords: cerebral palsy, developmental disorders, infant diagnostics infants, screening tests.